The Role of Professional Ethics in Organizational Health through the Mediation of Organizational Citizenship Behavior: Case Study of Yasuj Education - maryam shafiei sarvestani; tooraj derakhshanfar; Somayeh Mezginezhad (مجله علوم تربیتی, 2022)
IntroductionGiven the importance of organizational health in organizational development, efforts to improve the health of the organization is important, so it is necessary to pay attention to organizational health and the factors affecting it. Therefore, this study has investigated the role of professional ethics in organizational health mediated by organizational citizenship behavior.MethodThe statistical population of all education staff in Yasuj includes 550 people, of which 230 people were selected by available sampling using Morgan table. Data collection tools were professional ethics questionnaires of Gregory et al. (1990), Torkzadeh and Basiri organizational health (2015) and organizational citizenship behavior of Padsakov et al. (1990). Data were analyzed using SPSS24 and Smart-PLS statistical software and univariate t-test, Pearson correlation and structural equation modeling at the significance level of 0.05.ResultsThe results of one sample showed that the average score of professional ethics, organizational citizenship behavior and organizational health in general and its components (except for the component of perseverance and seriousness in work of professional ethics) in the education organization of the average theoretical score (3.00) as It is more meaningful. The results of Pearson correlation showed that there is a positive and significant relationship between the variables of professional ethics, organizational health and organizational citizenship behavior in general (p<0.001). The results of structural equation modeling showed that professional ethics has a positive and significant effect on organizational health (p = 0.05) but professional ethics has no significant effect on organizational health through organizational citizenship behavior. Therefore, organizational citizenship behavior does not play a mediating role in the relationship between professional ethics and organizational health.DiscussionThe results showed that the organizational citizenship behavior has no mediating role in the relationship between professional ethics and organizational health.This ineffectiveness may be due to the fact that effectiveness, coherence, and accountability as components of organizational health are not affected by the voluntary behaviors of individuals in the workplace, and such behaviors only attract and retain qualified personnel.Since organizational health is one of the most important signs of good working relationships between employees in the workplace and can guarantee success in the workplace of organizations by determining common values among employees, it can be said that a significant amount of professional ethics among employees has resulted. The behavior of organizational citizenship and its components are not seen in the mediation between the relationship between professional ethics and organizational health.